Analisis Penerapan Fitur Aplikasi Si Perlu dalam Meningkatkan Kedisiplinan Kerja Karyawan Puskesmas Kecamatan Yosowilangun Kabupaten Lumajang Perspektif Etos Kerja Islam - Adam Nasrullah; Muhammad Anwar Fuaddi; Moch Sutrisno; Aniqotuzzuhro' Fitriana (Medan Resource Center, 2023)
The Yosowilangun Health Center in improving employee discipline, implements an attendance system using the Si Need application feature with the aim of making it easier to control, supervise and evaluate the level of employee discipline. The Si Perlu application feature also has deficiencies in its work system, such as this application cannot be used when the lights are off, it is difficult to access employee attendance at the same time, and this application can be accessed if the employee's cellphone has a high capacity because this application has high RAM requirements as well. This study aims to determine the application of the Islamic work ethic to the employees of the district health center. Yosowilangun. This research uses qualitative techniques with descriptive research types. Data collection methods used are observation, literature study, interviews and documentation. The results of this study show that by enforcing absenteeism using the Si Need application feature at the Kec. Yosowilagun, employee discipline at work can be said to be stable and has increased.